Stres zawodowy pracowników nauki w świetle badań = Determinants of occupational stress among academic staff - presentation of the research - Chmielewska-Banaszak, Danuta; Giemza-Urbanowicz, Wioletta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The authors present the aim, tool, course and results of the research on occupational stress level among the academic staff from the University of Zielona Gora. The results of general stress level and intensification of particular stressors will be presented in a wider context: general consideration on occupational stress (called also job stress), i.e. causes, symptoms and effects; reflections on the specificity of scientific work from the perspective of psychological concepts of stress; review of research (relatively rare) on the stressors of scientific work; the attempt to define university as a work place. At the end the authors will present the conclusions concerning individual and institutional effects of occupational stress among academic staff.
Keywords: szkolnictwo wyższe; pracownicy naukowi; Uniwersytet Zielonogórski; stres zawodowy